Trafficking of Vietnamese women and girls for marriage in China - Heidi Stöckl; Ligia Kiss; Jobst Koehler; Dung Thuy Dong; Cathy Zimmerman (BMC, 2017)
Abstract Background Bride-trafficking has been a growing phenomenon in Southeast Asia, particularly in China, where one-child policies have resulted in demographic imbalances favoring males. Yet, empirical evidence about women and girls sold into marriage in China remains sparse. Methods This study describes the experiences of 51 Vietnamese women and girls as young as 14 in post-trafficking services who were sold into marriage in China. A consecutive sample of individuals from five services in Vietnam were invited to be interviewed within the first 2 weeks of admission. It is part of a wider dataset for research on the health of men, women, and children in post-trafficking services in Cambodia, Thailand, and Vietnam, the largest study to date on human trafficking and health. We calculated proportions for all variables and conducted bivariate analyses using Fisher Exact Tests for their associations with mental health disorders symptoms. Results Before leaving home, 31% (n = 15) participants were married. Participants reported high levels of sexual violence (n = 43; 86%) while trafficked and59% (n = 30) spent time in detention before returning to Vietnam. Once in post-trafficking care 52.9% (n = 27) reported probable depression, anxiety or post-traumatic stress disorders (PTSD), two women (4%) attempted suicide in the past month and 38 (75%) remained afraid of their trafficker. Ten (22%) became pregnant while trafficked, and seven (16%) were pregnant at the interview. Conclusions The cross-border bride trade between Vietnam and China raises complex policy issues, including questions about detention and immigration rights and strategies for supported return processes, including maternal and child health services. As the repercussions of China's absent female population will persist, Vietnam and China must grapple with the political and social conditions to implement prevention strategies, and resources for women who fall prey to this cross-border bride trade.